2018
DOI: 10.1016/j.vhri.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Drug Utilization Studies in Latin America: A Scoping Review and Survey of Ethical Requirements

Abstract: Background: Drug utilization studies (DUSs) are increasingly being conducted in Latin America, especially in countries with a universal healthcare coverage, to inform policies and decision making. The need for an ethical framework specific to DUSs in Latin America has been recognized. Objectives: To describe the ethical and/or legal requirements applicable to DUSs in Latin American countries with universal healthcare coverage. Methods: We conducted a nonsystematic scoping review on DUSs in this region, coverin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In addition, some countries demand a national approval to clinical trials' procedures, whereas others allow local evaluation. 32 During the pandemic, more than 25% of the Ethics Committees had their frequency of meetings reduced, which could lead to a longer time of wait for a remote consent approval. These differences and requirements may difficult the approval of remote consent, added to the difficulty of application, since there is an already mentioned lack of internet access by the general population.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some countries demand a national approval to clinical trials' procedures, whereas others allow local evaluation. 32 During the pandemic, more than 25% of the Ethics Committees had their frequency of meetings reduced, which could lead to a longer time of wait for a remote consent approval. These differences and requirements may difficult the approval of remote consent, added to the difficulty of application, since there is an already mentioned lack of internet access by the general population.…”
Section: Discussionmentioning
confidence: 99%
“…It According to a study published in 2018, in different countries in Latin America, regulatory approval prior to the beginning of the protocol is also necessary. This study also showed that the Helsinki declaration is used as a reference in all countries in the region, but that local and institutional policies are often heterogeneous and that data protection legislation varies among countries (Bergamasco, Arredondo Bisono, Castillon, & Moride, 2018).…”
Section: Clinical Trial Regulatory Issuesmentioning
confidence: 64%
“… 19,20 . Previous studies have identified that the available DUR data sources in LatAm countries were not used for decision‐making purposes, 12,13,21 and this reality must be changed.…”
Section: Discussionmentioning
confidence: 99%
“…DUR information is necessary for strategic planning and priority setting; for assurance of healthcare quality and design of quality improvement strategies; for management of diseases and injuries; and for implementing policies and programs focusing on the acquisition, reimbursement, pricing, and use of costeffective medicines in clinical settings. These strategies are especially important in settings with scarce healthcare resources and high disease burden, as in many LatAm countries.. 19,20 Previous studies have identified that the available DUR data sources in LatAm countries were not used for decision-making purposes, 12,13,21 and this reality must be changed.…”
Section: Type Of Data (Aggregate or Individual-level)mentioning
confidence: 99%